O controle social dos Planos Municipais de Educação: uma análise da participação de Conselhos Municipais de Educação de Goiás no processo de implementação dos PMEs - Borges, Guilherme Sousa (2022)
This thesis aims to analyze the participation of Municipal Councils of Education – understood as places of social representation in the sphere of political control of the State - in the processes of elaboration and approval of Municipal Education Plans, supporting the thesis that the level and quality of the participation of education councils in this processes is a determining factor for future actions of social control in the implementation of education plans. So, initially, a literature review sufficient to comprehend the proposed object was performed, and then a documentary and empirical research of a qualitative nature was carried out, in order to investigate the performance of education councils on the basis of public documents available for consultation and based on the highlighted theoretical contribution, using the Critical Discourse Analysis methodology for the construction of the text. After following the methodological path mapped out, it was realized that the Municipal Councils of Education investigated were part of both the elaboration and implementation process of Municipal Education Plans. However, this participation took place in an isolated way among members of the councils, and concrete evidence was missing to show whether there was participation in a collective and institutional perspective of the collegiate bodies in these processes. Such situation brings to light the conclusion that the presence of councils in the elaboration, monitoring and supervision of education plans took place only at the level of pseudo-participation, thus there’s the need for improvement of mechanisms for mobilization and social control by these collegiate bodies. Therefore, the supported thesis indicates that the lack of participation in a collective and institutional perspective on the part of education councils in the processes of elaboration of education plans ends up emptying their own actions of monitoring and supervision at the time of implementation of these plans, since there’s no, internally in the investigated councils, elements that demonstrate a relationship between their participation in the moments before and after the approval of the plans.